2018
DOI: 10.1038/s41598-018-20456-4
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhiza stimulates root-hair growth and IAA synthesis and transport in trifoliate orange under drought stress

Abstract: Root-hair growth and development regulated by soil microbes is associated with auxin. In this background, we hypothesized that mycorrhizal fungal inoculation induces greater root-hair growth through stimulated auxin synthesis and transport under water stress conditions. Trifoliate orange (Poncirus trifoliata) was inoculated with an arbuscular mycorrhizal (AM) fungus (Funneliformis mosseae) under well-watered (WW) and drought stress (DS) for 9 weeks. Compared with non-AM seedlings, AM seedlings displayed signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(66 citation statements)
references
References 38 publications
4
61
0
1
Order By: Relevance
“…Our results indicated that inoculation with AMF considerably augmented IAA (with the exception of MD stress) and GA 3 levels, but reduced zeatin (ZT, a cytokinin) in the leaves of C. bungei seedlings, exposed either to WW or drought stress conditions. This is in accordance with previous findings [22,66,99]. It implies that AMF could postpone leaf senescence and cause a quick adaptation to drought stress by influencing the auxin signal transduction.…”
Section: Discussionsupporting
confidence: 93%
“…Our results indicated that inoculation with AMF considerably augmented IAA (with the exception of MD stress) and GA 3 levels, but reduced zeatin (ZT, a cytokinin) in the leaves of C. bungei seedlings, exposed either to WW or drought stress conditions. This is in accordance with previous findings [22,66,99]. It implies that AMF could postpone leaf senescence and cause a quick adaptation to drought stress by influencing the auxin signal transduction.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, stimulation of biosynthesis and transport of IAA in roots of trifoliate orange under water restrictions were demonstrated [97]. Under drought conditions, AM colonization overexpressed PtYUC3 and PtYUC8 involved in IAA biosynthesis, and downregulated auxin efflux carriers (PtPIN1 and PtPIN3), while up-regulated auxin-species influx carriers (PtABCB19 and PtLAX2) in roots, leading to significantly higher IAA accumulation in mycorrhizal roots versus non-AM roots [97]. Together with higher IAA, colonized trifoliate orange plants showed a significant increase in MeJA, nitric oxide, and calmodulin in roots, supporting greater root adaptation of morphology as a crucial strategy for drought adaptation [93].…”
Section: Phytohormonal Changesmentioning
confidence: 87%
“…In a recent study, an increased content of indole-3-acetic acid (IAA) which is the dominant naturally occurring auxin was found in mycorrhizal tomato plants exposed to drought [91]. Similarly, stimulation of biosynthesis and transport of IAA in roots of trifoliate orange under water restrictions were demonstrated [97]. Under drought conditions, AM colonization overexpressed PtYUC3 and PtYUC8 involved in IAA biosynthesis, and downregulated auxin efflux carriers (PtPIN1 and PtPIN3), while up-regulated auxin-species influx carriers (PtABCB19 and PtLAX2) in roots, leading to significantly higher IAA accumulation in mycorrhizal roots versus non-AM roots [97].…”
Section: Phytohormonal Changesmentioning
confidence: 97%
“…Paenibacillus polymyxa could be developed to control pathogens and increase crop yield by producing IAA in field applications [6]. Additionally, inoculation of Funneliformis mosseae with trifoliate orange resulted in greater root-hair growth in density, length and diameter of seedling roots [7]. Overproduction of IAA improved nitrogen-fixing performances of endophytic microbes in culture or inoculated host plants [8].…”
Section: Introductionmentioning
confidence: 99%